Maqasid al-Shari'ah and AI Education: Waqf as a Tool for Knowledge Preservation and Technological Advancement - Adamu Abubakar Muhammad; Yusuf Isa Sawaba; Isma’il Iliyasu Danladi; Murjanatu Yusuf; Maryam Babani Muhammad (Yayasan Abdurrauf Cendekia Nusantara, 2026)
The recent, explosive advancements in AI is transforming global educational systems in providing opportunities of access, customization and knowledge generation, but at the same time has prompted concern of its governance ethics, epistemic bias and socio-digital disparities. The changes in Muslim societies require a revisit of Islamic knowledge traditions (particularly Maqasid al-Shari'ah, the higher objectives of Islamic law) to ensure technology adoption based on ethics, epistemic and social justice. This research study is to investigate the interplay between Maqasid al-Shari'ah, AIEducation and waqf (Islamic endowment) as a viable financing and institutional infrastructure of Islamic intellectual tradition that promotes the preservation of knowledge and innovations in the modern education sector. Applying a conceptual and qualitative approach using doctrinal analysis methodology, this research blends the insights from classical Islamic legal theory with current findings in the area of AIEducation and Islamic social finance, and also draws on comparable practices from waqf-based educational innovation in Malaysia and Indonesia. An integrated conceptual model where Maqasid al-Shari'ah serves as the ethical basis; waqf acts as a viable financing instrument; and AI as the technical driver in modern educational systems is built upon from the findings. The study indicates that Maqasid-driven waqf can alleviate common issues in educational finance, promote digital inclusion and enable an ethical implementation of AI in Muslim societies; and there are governing, regulatory and digital capacity constraints to be overcome to realize this model. This research is a testament of a strategic shift for sustainable preservation of knowledge, empowerment through technology and a socio-economic transformation in the Muslim world via an application of waqf for AIEducation.